TANGGUANG JAWAB CENDEKIA MUSLIM TERHADAP PERKEMBANGAN KEILMUAN ISLAM - J Sutarjo (Nizham Jurnal Studi Keislaman, 2014)
Science serves as a tool to dissect unknown fenoma nature to humans, so it takes a maximum sense of empowerment. Sense of empowerment to the maximum, then the new knowledge about the nature and its contents can be created. To given the importance of science to man, the human should strive to continue in discovering and developing the existing science, because the science is existed to provide a satisfying life, lift status and dignity as well as to establish a well-developed civilization that will be remembered by history. In line with the times, especially with the advent of globalization, the scientific world we experience many challenges, both internal and external challenges. Internal challenges come from Muslim intellectuals we are not able to create new science, making it less able to "adapt" to the environment and the nature of modernity. External challenges come from cultures that newly developed scientific secular morality does not pay attention and do not care about nature and the environment. To give the many challenges faced by today's Muslim intellectuals, indirectly it is a responsibility that must be endured, so that these challenges can be anticipated and appropriate solution found. In this regard, it is in this paper we discuss about: (1) How is the historicity of the Islamic scientific development of the world? (2) How is the responsibility of the Muslim intellectual world of Islamic scholarship?